Effects Of Aqueous Extract Of the Plant Datura metel Against Ascaridia galli Infection In Birds - Shaimaa A. Shlash; Samer A. Hasan (Kufa Journal for Veterinary Medical Sciences, 2016)
Objective: The present study was planned to identify the efficacy of Datura metel aqueous seeds extract against Ascaridia galli infection on body weight and some haematological parameters among in vivo in Birds. Methodology: The present study was carried out in advanced zoology laboratory/science college-Kufa university from February,2015 to January,2016. This study was carried out on 70 bird from layer hens type Domestic Pigeons naturally infected with A. galli , after determination LD50 on Ascaridia galli and certain that Datura metel without toxicity where used three groups were concentrations this material by two way the one orally 100 and 300 mg/kg respectively from body weight with Datura metel aqueous seeds extract and leave about other groups as positive control for 21 days. Result: The results showed that Datura metel aqueous seeds extract with concentration (300mg / kg) gave significantly (p<0.05) improving in body weight gain , increasing Hemoglobin values (Hb), Packed cell volume (PCV) and determination of Total erythrocyte count (TEC) to weeks (7,14 and 21) days following the concentration (100 mg / kg) which gave same result but lesser than above concentration compared with positive groups control (non-treated). Conclusion: The study proved that gave Datura metel aqueous seeds extract with concentration (300mg / kg) improved studied standers for naturally infested birds with Ascaridia galli after twice orally administration per day for continuous three weeks . Recommendations: Heading to use of medicinal plants for abundance, cheap price, more effective and side effects less.